Facing polyamorous lives: translation and validation of the attitudes towards polyamory scale in a Portuguese sample - Cardoso, D. (2018)
Consensual Non-Monogamies (CNMs) have been receiving the attention of academics, however attitudes towards polyamory (ATP) are still a new field of research. We aim at studying the reliability and validity of the ATP scale in a Portuguese sample. The present analysis utilized cross-sectional data from 609 volunteers that completed the online survey with a socio-demographic questionnaire; the ATP scale; the Modern Heterosexism subscale of the Multidimensional Scale of Attitudes Toward Lesbians and Gay Men; the Rosenberg Self-Esteem Scale; and the Willingness to Engage in Non-Monogamy Scale. After randomly splitting the sample (1:1) for cross-validation purposes, Exploratory (EFA) and Confirmatory factor analysis (CFA) were conducted using Principal Axis Factoring (PAF) and Maximum Likelihood Estimation, respectively. Cronbach's alpha and item-total correlations were used to determine the internal consistency of the scale. Feasibility and acceptability were examined in terms of missing values, floor and ceiling effects. The ATP proved to be reliable (Cronbach’s alpha > .80). In the current study, the final structure of the scale, proved through CFA, included 6 items aggregated in a single factor. This final 6-item measure proved to have convergent, divergent and concurrent criterion validity. Implications for research in polyamory and CNMs are discussed.